Tracking of chloramphenicol, erythromycin, and sulfamethoxazole antibiotic-resistant bacteria from untreated wastewater effluents to receiving river - Rahim Aali; Sepideh Baragh; Reza Fouladi Fard; Hassan Izanloo; Saeed Hosseinpoor; Jalhe Bagheri Hamzyan Olia; Roya Naser; Mohsen Mehdipour Rabori (Environmental Health Engineering and Management, 2019)
Background: The aim of this study was to investigate the frequency and type of bacteria resistant to chloramphenicol (CHL), erythromycin (E), and sulfamethoxazole (SXT) antibiotics from untreated wastewater effluents to receiving river. Methods: In total, 32 samples were taken from eight sites located in the raw wastewater to the downstream of the receiving Ghotor river in Khoy city. Resistant microorganisms were studied through modified HPC method and CLSI standards. Different and specific colonies were selected and re-cultured in R2A culture medium and enough colonies were used for DNA extraction. Bacterial 16sr RNA target gene was amplified and sequenced. Pseudomonas sp., Comamonas sp.,and Thiobacillus sp. were predominant bacterial species identified in water samples. Also, antibiotic-resistant genes (ARGs) including sul1, ermB, and cmlA1 were tracked by PCR. Results:The average total number of antibiotic-resistant bacteria (ARB) increased in the downstream (2.4×102 to 2.6×104 CFU/100 mL). The comparison of the results related to the river’s upstream and downstream also indicated a significant difference between ARB and ARGs contents (P<0.05). The average number of bacteria resistant to SXT, E, and CHL antibiotics was obtained to be 2.3×104, 2.3×104, and 3.4×104 CFU/mL, respectively. Finally, the evaluation of water revealed that only the aeration lagoon was able to decline the number of CHL-resistant bacteria (88.9%) while this process increased the number of SXT- (51%) and E- (16%) resistant bacteria.The lowest and highest percentages of the identified genes were related to ermB (12.5%) and sul1 (81.25%), respectively. Conclusion: According to the results, wastewaters play an important role in releasing ARB and their antibiotic resistance genes to downstream of Ghotor rivers in Khoy city.